BIOLOGICAL CHARACTERISTICS OF THE CAUSATIVE AGENT OF TUBERCULOSIS IN PATIENTS WITH PULMONARY TUBERCULOSIS - Jumayev Mukhtor Fatullayevich (Scholar Express Journals, 2021)
This paper presents the materials of microbiological studies of 449 bacteriareleasing bacteria tested for DST and who were hospitalized for various forms of pulmonary tuberculosis. When analyzing resistant strains of MBT, it was found that 50 (17.5%) were mono-resistant, 76 (26.7%) strains of MTB were poly-resistant, i.e., resistant to at least two anti-tuberculosis drugs and 159 (55.8%) were multi-resistant. Conclusions: A high percentage of primary drug resistance was established: MBT with multidrug resistance were identified in 38 (44.7%) previously untreated patients. Most of the isolated strains of mycobacterium had drug resistance simultaneously to 3-4 drugs
Keywords: Tuberculosis; Drug Resistance; MDR; Mono-Resistance.